Physics Teaching in Croatian Elementary and High Schools during the Covid-19 Pandemic - Ivana Štibi; Mojca Čepič; Jerneja Pavlin (Center for Educational Policy Studies Journal)
In spring 2020, 916 elementary schools and 443 high schools were closed in Croatia due to the Covid-19 pandemic and remote teaching was introduced. This had an impact on physics teaching as an experimental subject. In addition to positive aspects concealed in new experiences and work perspectives, the sudden transition from conventional face-to-face teaching to a remote format had an undeniable negative impact on physics teaching in elementary and high schools. In order to mitigate the effects and provide a detailed insight into the problems that arose during this transition, we conducted a quantitative study among teachers of physics in elementary and high schools in Croatia, with the aim of identifying logistical and technical problems and challenges in physics teaching during the Covid-19 pandemic. An online questionnaire with five parts (general data, teaching physics during the Covid-19 pandemic, experiments, sociological component, exchange of experience) was completed by 178 Croatian teachers. The results irrefutably point to the flexibility and responsiveness of physics teachers, an increase in the teachers’ workload, a lack of the experimental work that forms an essential part of the subject of physics, and a lack of teacher knowledge (in ICT), skills and equipment for conducting distance teaching. However, it also emerged that online teaching, if carefully designed and individualised, can stimulate additional commitment and interest in the subject among students. The paper presents the research findings in detail, with the aim of helping physics teachers to plan further teaching more effectively as and if the pandemic progresses.